MANAJEMEN PRODUKTIF DI BADAN AMIL ZAKAT NASIONAL (BAZNAS) KABUPATEN JEMBER - Ningrum, Nurita Kustiari (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Poverty is a challenge for every country, especially in developing countries like Indonesia. This poverty occurs due to the loss of rights or wealth that is difficult to return, and the pressure of needs that exceed their limits so that the amount of expenditure is very large. Economic factors that have a close relationship with various problems, especially for some underprivileged people who face an inadequate life. Implementation can be achieved by managing productive zakat funds. Therefore, management is needed in managing productive zakat funds such as planning, organizing, mobilizing, and supervising. With good management, zakat management will be productive. The development of businesses carried out by mustahik will increase mustahik's income and change mustahik's status to muzakki. Based on the research context above, the focus of this research is: 1) How is the planning of productive zakat distribution at BAZNAS Jember Regency. 2). How is the implementation of productive zakat distribution at BAZNAS Jember Regency. 3). How is the evaluation of productive zakat distribution at BAZNAS Jember Regency? Based on the existing focus and objectives, this study uses a qualitative approach, the informant collection technique uses purposive sampling. Data collection techniques through observation, interviews, and documentation. The validity of the data used in the study is source triangulation. Based on the results of the research that has been conducted. 1). The planning of zakat distribution at the National Zakat Agency (BAZNAS) of Jember Regency has been in accordance with the zakat management guidelines from the central BAZNAS. 2). The implementation of the distribution of productive zakat at BAZNAS Jember Regency is in accordance with the provisions of Islamic law which manages zakat to create a prosperous society in poverty alleviation. Namely by: first, Providing counseling to recipients of productive zakat. Counseling is provided to ensure that the mustahik's business can run and develop. Second, BAZNAS Jember Regency distributes productive zakat funds through a business capital provision program. BAZNAS Jember Regency provides business capital assistance as a grant fund. So, the mustahik do not need to return it. For independent business activities, the mustahik receives an average of Rp. 1,000,000, according to the needs of the mustahik's business. Furthermore, BAZNAS Jember Regency carries out monitoring, control, and supervision. This supervision is carried out to find out the development of productive zakat recipients by using data from the WA group that was previously created. 3). Evaluation carried out by BAZNAS Jember Regency through fund management reports and without any special evaluation. BAZNAS Jember Regency also explained the obstacles faced in this evaluation activity such as: Low Public Awareness, Lack of Government Support, Minimal Funding Sources, Limited human resources (HR). And until now, the results of the business capital provision program have not had any mustahik who have changed their status to muzaki